ALIMENTAÇÃO, CORPO E SUBJETIVIDADES NA EDUCAÇÃO FÍSICA E NA NUTRIÇÃO: O RANÇO DA ADIPOSIDADE E A ASCENSÃO DOS MÚSCULOS - Juliana Brandão Pinto de Castro; Rafael da Silva Mattos; Michelle Delboni dos Passos; Fernanda Silva Dias de Aquino; Jeferson José Moebus Retondar; Anderson dos Santos Machado (Universidade do Estado do Rio de Janeiro, 2016)
The aim of this paper is to discuss issues related to body image among undergraduate students in Physical Education and Nutrition programs at a public university in the city of Rio de Janeiro. This study has a socio-anthropological nature in the field of Public Health. The methodological strategy was to articulate participant observation and informal and formal interviews with these students. We found that the students feel pressured to be role models of good eating habits and body practices; in other words, to have behaviors considered as healthy. In addition, they must have a body image that meets the current esthetic standards. This is a discourse that prevails among them, both inside and outside the academic environment. Values relative to youth, sex and body esthetics are mobilized in such environment and associated with social life, distinctive positions in a strongly hierarchical society, and reactions to social norms and rules, among other features in the consumer society, where body image worship tends to be hegemonic. DOI: 10.12957/demetra.2016.21995